Biochemical Characterization and N-terminomics Analysis of Leukolysin, the Membrane-type 6 Matrix Metalloprotease (MMP25): CHEMOKINE AND VIMENTIN CLEAVAGES ENHANCE CELL MIGRATION AND MACROPHAGE PHAGOCYTIC ACTIVITIES - Starr, Amanda E. (American Society for Biochemistry and Molecular Biology, 2012)
The neutrophil-specific protease membrane-type 6 matrix metalloproteinase (MT6-MMP)/MMP-25/leukolysin is implicated in multiple sclerosis and cancer yet remains poorly characterized. To characterize the biological roles of MT6-MMP, it is critical to identify its substrates for which only seven are currently known. Here, we biochemically characterized MT6-MMP, profiled its tissue inhibitor of metalloproteinase inhibitory spectrum, performed degradomics analyses, and screened 26 chemokines for cleavage using matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry. MT6-MMP processes seven each of the CXC and CC chemokine subfamilies. Notably, cleavage of the neutrophil chemoattractant CXCL5 activates the chemokine, thereby increasing its agonist activity, indicating a feed-forward mechanism for neutrophil recruitment. Likewise, cleavage also activated CCL15 and CCL23 to increase monocyte recruitment. Utilizing the proteomics approach proteomic identification of cleavage site specificity (PICS), we identified 286 peptidic cleavage sites spanning from P6 to P6′ from which an unusual glutamate preference in P1 was identified. The degradomics screen terminal amine isotopic labeling of substrates (TAILS), which enriches for neo-N-terminal peptides of cleaved substrates, was used to identify 58 new native substrates in fibroblast secretomes after incubation with MT6-MMP. Vimentin, cystatin C, galectin-1, IGFBP-7, and secreted protein, acidic and rich in cysteine (SPARC) were among those substrates we biochemically confirmed. An extracellular “moonlighting” form of vimentin is a chemoattractant for THP-1 cells, but MT6-MMP cleavage abolished monocyte recruitment. Unexpectedly, the MT6-MMP-cleaved vimentin potently stimulated phagocytosis, which was not a property of the full-length protein. Hence, MT6-MMP regulates neutrophil and monocyte chemotaxis and by generating “eat-me” signals upon vimentin cleavage potentially increases phagocytic removal of neutrophils to resolve inflammation.